Technologies of Organizational Analysis: Charting ‘Organization’ as a Practical and Epistemic Object - Vikkelsø, Signe (STS Encounters, 2016)
Historians of science Lorraine Daston and Peter Galison argue that any science “must deal with the problem of selecting and constituting ‘working objects’ as opposed to the too plentiful and too various natural objects” (2007: 19). In the paper, which is written for my inaugural lecture at Copenhagen Business School, I analyze the fate of the organization chart as a central working object in classic organization and management theory. By contrasting the way it was once used and discussed by classic authors such as Luther Gulick and Lyndon Urwick (1937) with the way organization charts were used in contingency theory and finally with their disappearance in contemporary organization studies and altered role in the selfrepresentation of modern organizations, I describe a history of changing forms of visualization in organization theory and managerial practice. I also discuss the practical and political consequences of this development.